Konsep Kesakralan dalam Desain Arsitektur Peter Zumthor: Studi Kasus: Saint Benedict Chapel dan Bruder Klaus Chapel - Renaldi, Natanniel; Sudradjat, Iwan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2025)
Title: The Concept of Sacredness in the Architectural Design of Peter Zumthor; Case Study: Saint Benedict Chapel and Bruder Klaus Chapel The sacredness of space is crucial for Catholic worship, allowing the congregation to feel God's presence. Peter Zumthor's architecture prioritizes spatial ambiance by engaging all senses, using appropriate materials, and harmonizing buildings with their sites. His Saint Benedict Chapel and Bruder Klaus Chapel exemplify his design principles. This study uses a qualitative approach and descriptive analysis to explore Zumthor's design concepts and their impact on sacredness. Both chapels showcase his skill in using light, materials, and spatial forms to create a sacred atmosphere. Light symbolizes God's presence through beams, movement, and contrasts, with dynamic lighting in Saint Benedict Chapel and dark shelter quality in Bruder Klaus Chapel. Materials are chosen for their sensory impact and aging process. Saint Benedict Chapel features warm wood and delicate detailing, while Bruder Klaus Chapel uses charred wood for a unique aroma and texture. The distinct forms of both chapels create a contemplative atmosphere and reinforce their function as places of worship.